Taklik Talak as a Form of Reforming Islamic Family Law in Indonesia - Sulfianti Irma Pai'pinan; Rameyza Elya Yulianti; Kurniati Kurniati (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
In the context of family law in Indonesia, taklik talak (divorce by mutual consent) is a legal reform that aims to protect the rights of wives and address the imbalances that often occur in divorce cases. However, the effectiveness of this instrument is often hindered by low legal literacy and cultural stigmas that perceive taklik talak as a mere formality or even an